1993
DOI: 10.1002/aja.1001980207
|View full text |Cite
|
Sign up to set email alerts
|

Collagen type VI in neural crest development: Distribution in situ and interaction with cells in vitro

Abstract: We have examined the spatiotemporal distribution of collagen type VI (Col VI) during neural crest development in vivo and its ability to promote neural crest cell attachment and migration in vitro. An affinity purified antiserum and chain-specific monoclonal antibodies against chicken Col VI were employed to immunolocalize the collagen in tissue sections and by immunoblotting. At stages of initial neural crest cell migration, the al(V1) and 012(VI) chains were immunolocalized in apposition with basement membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 46 publications
(69 reference statements)
3
29
0
Order By: Relevance
“…3). Type VI collagen has been shown to be involved in both the migration and proliferation of cells (Perris et al, 1993;Pfaff et al, 1993;Atkinson et al, 1996). In view of these data, our observations suggest that CT cells synthesize the majority of the type VI collagen present in the AV cushions and that type VI collagen may play a role in modulating normal CT cell migration and proliferation.…”
Section: Resultssupporting
confidence: 49%
See 1 more Smart Citation
“…3). Type VI collagen has been shown to be involved in both the migration and proliferation of cells (Perris et al, 1993;Pfaff et al, 1993;Atkinson et al, 1996). In view of these data, our observations suggest that CT cells synthesize the majority of the type VI collagen present in the AV cushions and that type VI collagen may play a role in modulating normal CT cell migration and proliferation.…”
Section: Resultssupporting
confidence: 49%
“…Structural considerations predict that a 1:1:1 [␣1(VI): ␣2(VI): ␣3(VI)] type VI collagen chain assembly is required for the formation of a stable microfibrillar collagen network Heckmann et al, 1992). In vitro studies suggest type VI collagen, in its native state, participates in cell adhesion and migration through interactions with members of the integrin receptor family or the NG2 proteoglycan (Aumailley et al, 1989(Aumailley et al, , 1991Perris et al, 1993;Pfaff et al, 1993;Burg et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The findings support the hypothesis that type VI collagen is present in both filamentous and fibrous matrices, and that networks of type VI collagen may serve as a fine scaffolding that facilitates the integration of types I and III collagen into the developing fibrous matrix. Type VI collagen in developing tissue has also been studied in the neural crest development of the chick embryo (PERRIS et al, 1993), where type VI collagen was described as a primary component of the extracellular matrix deposited along neural crest migratory pathways, or as a migratory substrate. ZHANG et al (1994) have reported the quantification and localization of mRNA for human type VI collagen.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to serving a structural role, type IV collagen interactions with cells have been implicated in affecting processes such as cell adhesion, migration, and differentiation (41). Increased levels of type IV collagen are found to occur along certain pathways during development (42,43), tissue remodeling after injury (44,45), and tumor invasion (46,47). In normal adult cornea, ␣3/␣4(IV) chains of collagen IV are found in the epithelial basement membrane (48,49).…”
Section: Expression and Post-translational Modification Of Aplp2 In Cmentioning
confidence: 99%